Failure and Instability Mechanism of Small Coal Pillar Induced by Weakly Cemented Lateral Overlying Strata in Gob-Side Working Face - Yingyu Tang; Deyuan Fan; Xuesheng Liu; Yunliang Tan; Yifeng He; Penghua Wu; Hu Song; Yu Zhang; Guangjin Shi (Advances in Civil Engineering)
Small coal pillar instability induced by lateral overlying strata in gob-side working faces is an engineering problem, which is one of the main bottlenecks restricting safety production. This study investigated the stability and control technologies for small coal pillars through theoretical analysis, numerical simulation, and field testing. First, mechanical parameters of coal and rock mass were determined via numerical simulation. Based on field monitoring, the deformation and failure characteristics in small coal pillars caused by movement of weakly cemented lateral overlying strata were analyzed. The results showed that an “inverted trapezoidal” bearing zone formed above the coal pillar along the working face advancing direction. The advance abutment pressure reaches 39.8 MPa, representing a 62.31% increase compared to the original rock stress, with a maximum stress concentration coefficient of approximately 2.45. A structural mechanics model of the “coal pillar overlying weakly cemented strata” system was established by elastoplastic theory. Combined with field conditions, key technologies for small coal pillars were proposed. A “pressure relief-grouting” coordinated control strategy was developed and verified by field tests.